Drivers and enablers for the implementation of industry 4.0 technologies in performance measurement systems: a systematic review - Lopes, Marcelo Almir; Martins, Roberto Antonio (Brazilian Journal of Production Engineering, 2024)
The ever-changing business landscape and evolving stakeholder requirements, coupled with the influx of complex real-time data, require more dynamic and resilient performance measurement systems (PMS). Industry 4.0 (I4.0) technologies offer significant potential in enhancing PMS. However, implementing these technologies into PMS is a complex process that faces various barriers. This article presents the findings of a systematic literature review (SLR) that explores the essential factors for implementing I4.0 technologies in PMS. Through examining 33 documents, the study highlights several key drivers, including the importance of continuous real-time monitoring of PMS for decision-makers, the potential for enhanced agility, and the prospects for improved productivity and efficiency. Additionally, the research identifies significant enablers, such as financial capacity for investment and the availability of a qualified workforce. Therefore, this study contributes to a better understanding of the drivers and enablers that support the adoption of I4.0 technologies in PMS.